Factors Negatively Affecting the Development of The Agricultural Economy of Our Country - Maftuna Ermatova Arslonbek kizi (International Journal of Scientific Trends, 2023)
Agricultural economy maximally satisfies the demand for food security of countries. There is a sector with a developed economy, which shows an increase in the income of the population and the development of the country. If there are factors that have a negative impact on this, it is the need of the hour to eliminate them by developing strategic projects.